How important is sustainability for visitors of rock and pop festivals? Insights from a broad audience analysis in Germany - Matthias Johannes Bauer; Tom Naber; Lea Sophie Michel (Agora International Journal of Economical Sciences (AIJES), 2024)
The study examines the significance of sustainability among festival attendees (N = 3,503), revealing that a substantial majority of 90.4% do not consider it a primary factor in their festival experience. The analysis highlights demographic influences, indicating that factors such as age, gender, and educational background have minimal impact on the perceived importance of sustainability. The paper synthesizes these findings, concluding that sustainability is not a central aspect of the festival experience for most visitors. Why is this the case? The answer lies in a key aspect of the experience that guests seek at festivals: escapism. The study suggests that traditional approaches, such as strict regulations on non-sustainable practices, may be counterproductive. Instead, it advocates for the development of innovative nudging strategies that promote sustainable behaviors while preserving the escapist nature of festivals. By fostering a culture of engagement rather than prohibition, event organizers can enhance the integration of sustainability into the festival experience, ultimately encouraging more responsible participation among attendees.
Keywords: 330; festivals; sustainability; escapism; nudging strategies